Two new species of Pneumia Enderlein (Diptera, Psychodidae, Psychodinae) from the Palaearctic region - Omelková, Markéta; Ježek, Jan (Zootaxa, 2012)
We propose two new species: Pneumia kabelaki sp. nov. from the Czech Republic and P. toubkalensis sp. nov. from Mo-rocco. Pneumia isabellae (Wagner), a new record for Slovenia, is redescribed. Differential diagnoses are included and im-portant diagnostic characters illustrated. The concept of some Palaearctic Pericomaini is discussed and all describedspecies and subspecies of the genus Pneumia Enderlein are listed with a report of 34 new combinations. The followingspecies are transferred from Pericoma Haliday to Pneumia: Pneumia ariegica (Vaillant), P. borealis (Berdén), P. califor-nica (Kincaid), P. canariensis (Tonnoir), P. delphinensis (Georges), P. extricata (Eaton, P. hirticornis (Tonnoir), P. isabel-lae (Wagner), P. jungi (Vaillant), P. longistylis (Mirouse), P. marinkovicae (Krek), P. omogoensis (Tokunaga & Komyo),P. propinqua (Satchell), P. rivularis (Berdén), P. sziladyi (Szabó), P. thomasi (Vaillant), P. vandeli (Mirouse). In addition,nineteen species are transferred from Satchelliella Vaillant to Pneumia: Pneumia arvernica (Vaillant), P. balcanica (Krek),P. bosniaca (Krek), P. bucegiana (Vaillant), P. dissimilis (Krek), P. distincta (Krek), P. incurvata (Krek), P. joosti (Wag-ner), P. montenegrina (Krek), P. narsanica (Vaillant & Joost), P. pyrenaica (Vaillant), P. sanae (Krek), P. sandaliae (Sala-manna), P. scotiae (Curran), P. stammeri dinarica (Krek), P. stylata (Vaillant, 1973), P. tarae (Krek), P. ussurica (Wagner) and P. vaillanti (Wagner).